A Tale of 2 Morphologies: Diagnostic Pitfalls in TFEB-Associated Renal Cell Carcinomas, Including a Novel NEAT1-TFEB Fusion. (February 2021) - Sharma, Aarti E.; Parilla, Megan; Wanjari, Pankhuri; Segal, Jeremy P.; Antic, Tatjana
Aims: Translocation-associated renal cell carcinomas (RCCs) have been extensively subcharacterized in recent years, such that each is largely recognized by the 2016 World Health Organization as categorical neoplastic entities in the genitourinary tract. Those belonging to the t (6;11) family of tumors classically have a fusion between TFEB and MALAT1/α, and display a particular histomorphology. Specifically, they show a biphasic population of both small and large epithelioid cells, the smaller component of which surrounds basement membrane-type material. Despite this apt description, the tumors have variable morphology and mimic other RCCs including those with TFE3 translocations. Therefore, a high degree of suspicion is required to make the correct diagnosis. Methods: The 2 cases described in this article were of strikingly different appearance, and initially considered consistent with other non-translocation–associated renal tumors. These included clear cell RCC (CCRCC), perivascular epithelioid cell tumor (PEComa), and other eosinophilic RCCs (mainly papillary RCC type 2). Results: Using RNA sequencing techniques, they were found to harbor distinct pathogenic rearrangements involving the TFEB gene, namely, fusions with CLTC and NEAT1 (the latter partnering heretofore never reported). Conclusions: These alterations manifested in 2 notably dissimilar lesions, underscoring the importance of including this family of carcinomas in the differential of any renal neoplasm that does not display immunophenotypic characteristics consistent with its morphology.